Local management with methotrexate of cesarean scar ectopic pregnancy with live embryo guided by transvaginal ultrasound: A case report - Leite,Juliana de Freitas (2016)
Summary Cesarean scar ectopic pregnancy is a rare type of ectopic pregnancy with high morbidity and mortality. Use of conservative conducts, including medical management with methotrexate, has avoided mutilating surgeries such as hysterectomy and spared the fertility of women. We report the case of a 30-year old patient with a cesarean scar ectopic pregnancy, with a live embryo, who was treated locally with transvaginal ultrasound-guided injection of methotrexate, complemented with various doses of systemic methotrexate.